High phenanthrene degrading efficiency by different microbial compositions construction - Zhou, Guoyan; Qiao, Hongtao; Liu, Yandong; Yu, Xiongsheng; Niu, Xiang (Frontiers in Microbiology, 2024)
Microbial remediation has become the most promising technical means for the remediation of polycyclic aromatic hydrocarbons (PAHs) non-point source contaminated soil due to its low cost of treatment, complete degradation of pollutants, and in-situ remediation. Phenanthrene was chosen as the representative of PAHs and in order to demonstrate the phenanthrene degrading microbial diversity, the strains capable of degrading phenanthrene were isolated and screened from the sedimentation sludge and the bottom sludge of oil tank trucks, and the dominant strains with a good degrading effect on phenanthrene were sequenced. Results showed even more than 50% of phenanthrene was degraded in all samples, the composition of PAH-degrading bacteria was diverse, and different environments constructed different functional microbial groups, which resulted in the microbial adapting to the diversity of the environment. Finally, a series of bacterial species with phenanthrene-degrading functions such as Achromobacter, Pseudomonas, Pseudochelatococcus, Bosea was enriched after nine transferring process. Therefore, when we studying and enriching the functional degrading microbes of phenanthrene or other pollutants, more concern should be paid in not only the degradation rate, but also the diversity variation of microbial community composition..